Avances en la Caracterización Clínica y Terapéutica del Lupus Eritematoso Sistémico. - Bonilla Muñoz, Katherine Alejandra (2024)
The following research includes significant advances in the clinical and therapeutic characterization of Systemic Lupus Erythematosus (SLE) based on updated articles between 2018 and 2023, highlighting key data for the understanding, diagnosis, and management of this complex, multidisciplinary disease. Through a systematic literature review, we analyzed recent studies to assess progress in pathophysiology, risk factor identification, and therapeutic strategies for SLE. The findings demonstrate an evolution in the understanding of the pathophysiology of SLE, highlighting the importance of abnormal immune responses, the creation of autoantibodies, and complement with their respective activation. This improved understanding facilitated updating the diagnostic basis and knowledge of the disease along with its classification, allowing earlier and more accurate interventions. The research identified multiple risk factors associated with SLE, including genetic predispositions, environmental exposures, and sociodemographic factors. It underscores the importance of a comprehensive approach to disease management that considers these diverse factors. In terms of treatment, progress has been made in the development and implementation of pharmacological therapies, including immunosuppressants, biologics, and targeted therapies, as well as nonpharmacological strategies that significantly improve the quality of life of patients. This review seeks to support the promotion of interdisciplinary research, analyzing diagnostic protocols, integrating risk factor assessment into medical practice, and optimizing the therapeutic management of SLE and consequently optimizing the diagnosis, treatment, and subsequent prognosis for patients with SLE, reflecting the importance of a personalized and evidence-based approach in the management of this disease.